2018
DOI: 10.26832/24566632.2018.0304015
|View full text |Cite
|
Sign up to set email alerts
|

A review on aflatoxins in stored grain food, their sources, mechanisms and possible health hazard

Abstract: The aflatoxin producing fungi Aspergillus flavus, Aspergillus parasiticus, and Aspergillus nomius are highly hepatotoxic, carcinogenic and immunosuppressive which can spread quickly in environment and contaminate stored food. It can lead to serious threats to both human and animal health hazards by causing various diseases. Aflatoxin can breakdown DNA and causes genomic damage during cell division, leading to cancer even death where these breakdown products accumulate in the liver. The chemistry and biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…The effects of AFs on the BBB were also investigated such that the outcomes showed that AFs (in particular AFB1) could alter mitochondrial gene expression profile in the human BBB cells model ( 243 ). More interestingly, AFB1 could inhibit the electron transport chain function, affect ATP synthesis and dysregulate key genes in mitochondria ( 243 ), leading to genetic mutations and DNA damage ( 244 ).…”
Section: Afs and Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…The effects of AFs on the BBB were also investigated such that the outcomes showed that AFs (in particular AFB1) could alter mitochondrial gene expression profile in the human BBB cells model ( 243 ). More interestingly, AFB1 could inhibit the electron transport chain function, affect ATP synthesis and dysregulate key genes in mitochondria ( 243 ), leading to genetic mutations and DNA damage ( 244 ).…”
Section: Afs and Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…AFB1 mechanism of action implies inhibition of the ETC between CIII and CIV with a wide spectrum causing mutations and other DNA damage (Sharma et al 2018). T-2 mycotoxin was found to reduce activity of mitochondrial complexes III, IV and V. Also, T-2 activated apoptosis pathway caspase-9 and 3 in chondrocytes and mitochondrial cytochrome c release (Liu et al 2014).…”
Section: Complex IVmentioning
confidence: 99%
“…Protein loss is linked with uncontrolled cell growth and tumor formation (Hu et al 2015). AFB1 has been found to inhibit the Electron Transport Chain (ETC) at the cytochrome oxidase level, precisely between cytochrome b1 and c, inducing also the release of different ROS species (Theumer et al 2018;Sharma 2018). Also, affinity of AFB1 for mitochondrial genes is 3 or 4 times higher than for nuclear DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins are the main mycotoxins synthesized by Aspergillus flavus, A. parasiticus and A. nomius [37][38][39]. Aflatoxin-related contamination by fungi can occur in food and feed products (e.g., cocoa, spices, figs, rice, wheat, maize, sesame seeds, millet, and groundnuts) during the processes before and after harvesting [40][41][42][43][44][45][46][47][48][49][50][51][52]. Moreover, AF can contaminate commercial products such as cosmetics, cooking oil, and peanut butter.…”
Section: Introductionmentioning
confidence: 99%